An overview of the genus Radiospongilla (Porifera, Spongillida) with description of a new species from Australia - Pronzato, R.; Manconi, R. (Zootaxa, 2020)
A new species of freshwater sponges is described from Australia. The new species Radiospongilla fungosa is characterized by the following traits ‘megascleres microspiny stout oxeas with scattered, small, simple spines except tips’, and by having ‘gemmuloscleres long, slim, spiny strongyles with scattered simple spines and hooked spines clustered at tips’, ‘gemmular theca with 2 layers of gemmuloscleres radially and tangentially arranged’, ‘pneumatic layer irregularly filamentous network (near inner layer) and thin laminae irregularly arranged (towards outer layer)’. We discuss the relationships of the new species to other members of the genus both from Australia, particularly North-Western Australia, and from other biogeographic regions on the basis of diagnostic morphotraits. An overview on the taxonomy, biogeographic pattern and phylogeny of the genus is supplied and updated to present, together with an updated identification key for Australia species. The diagnosis of the genus Radiospongilla is emended.